FOLIC ACID AND ITS ROLE IN THE REPRODUCTIVE HEALTH OF WOMEN WITH POLYCYSTIC OVARY SYNDROME - Архипкіна Т. Л. (World of Medicine and Biology, 2015)
The article deals with the biological role of folic acid and its derivatives in the reproductive function of women. Is accented the attention to the impact of folic acid deficiency in the formation of hyperhomocysteinemia and endothelial dysfunction in patients with polycystic ovary syndrome, and are presented the results of their own observations. Found, that women with PCOS have a folic acid deficiency various degree of expressiveness and increased levels of endothelin-1. A negative correlation between folate and homocysteine concentration in plasma was found. The need to determine the level of folic acid for the timely conduct of events aimed at preventing the development of endothelial dysfunction was indicated.
Keywords: polycystic ovary syndrome; folic acid; homocysteine; endothelin-1